T Cell Responses to BA.2.86 and JN.1 SARS-CoV-2 Variants in Elderly Subjects - Irene Segato; Dalila Mele; Greta Forlani; Daniela Dalla Gasperina; Mario U. Mondelli; Stefania Varchetta (Vaccines)
Background/Objectives: New SARS-CoV-2 variants are continuously emerging, making it essential to assess the efficacy of vaccine-induced immune protection. Limited information is available regarding T cell responses to BA.2.86 and JN.1 variants, particularly in elderly individuals. Methods: We evaluated T cell and total IgG responses against the receptor-binding domain (RBD) of the ancestral SARS-CoV-2 strain, as well as BA.2.86 and JN.1 omicron subvariants, in two groups of subjects. One group consisted of SARS-CoV-2-exposed elderly individuals who were fully vaccinated with the BNT162B2 mRNA vaccine, with a booster dose of the updated 2023–2024 COVID-19 vaccine (XBB.1.5) at least 15 days after receiving a booster dose of the updated 2023–2024 COVID-19 vaccine. The second group consisted of healthcare workers who were unexposed to SARS-CoV-2 one month after the booster dose of the first-generation BNT162b2 mRNA vaccine. T cell activation-induced markers (AIM) and IFN-γ secretion were evaluated by flow cytometry and ELISpot assays, respectively. Results: Elderly subjects showed reduced IgG levels against JN.1 compared with the ancestral strain. BA.2.86 stimulation resulted in lower IFN-γ levels in the elderly versus the COVID-19-naïve group. AIM analysis showed that among T cells, CD4+ were the most responsive, with a reduced proportion of JN.1-reactive CD4+ T cells compared with the ancestral strain in the SARS-CoV-2-unexposed group. Despite receiving the updated booster, the elderly group showed reduced CD4+ T cell reactivity to BA.2.86. Conclusions: The XBB.1.5-containing vaccine induced lower CD4+ T cell responses against BA.2.86 in the elderly. CD4+ T cells from BNT16b2-vaccinated, COVID-19-naïve subjects recognized ancestral and BA.2.86 RBD strains while showing reduced responses to JN.1. These results emphasize the need for tailored vaccine strategies for emerging variants, particularly in vulnerable populations.